2013
DOI: 10.1002/cjoc.201200986
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of the Proposed Structures of Orisuaveolines A and B

Abstract: First total synthesis of the proposed structures of β-indoloquinazoline alkaloids orisuaveolines A and B is reported. The key steps of the synthesis included a Pictet-Spengler reaction to build a six-member lactam which further transformed into target molecular by a one-pot condensation. This synthesis provided an access to the proposed structures of orisuaveolines A and B in a short and convenient manner from inexpensive, commercially available starting materials. The structures of our synthesized products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Li and co‐workers reported the first total synthesis of β‐indoloquinazoline alkaloids Orisuaveloine A 158 and Orisuaveloine B 160 . The synthesis started with the reaction of tryptamine derivatives ( 155 a or 155 b ) with triphosgene in the presence of triethylamine to generate isocyanate in‐situ , which underwent intramolecular nucleophilic substitution in the presence of hydrogen bromide catalyst to provide tetrahydro‐β‐carboline‐1‐one ( 156 a or 156 b ) (Scheme ).…”
Section: β‐Carboline Fused Heterocycles Synthesized Via Post‐pictet‐smentioning
confidence: 99%
“…Li and co‐workers reported the first total synthesis of β‐indoloquinazoline alkaloids Orisuaveloine A 158 and Orisuaveloine B 160 . The synthesis started with the reaction of tryptamine derivatives ( 155 a or 155 b ) with triphosgene in the presence of triethylamine to generate isocyanate in‐situ , which underwent intramolecular nucleophilic substitution in the presence of hydrogen bromide catalyst to provide tetrahydro‐β‐carboline‐1‐one ( 156 a or 156 b ) (Scheme ).…”
Section: β‐Carboline Fused Heterocycles Synthesized Via Post‐pictet‐smentioning
confidence: 99%
“…More quantitative models use the Eigen-Tamm formulation to quantify the association of ion pairs in both solvent-separated ion-pairs and contact ion-pairs. [10,11] The most-studied lyotropic biochemical effects involve the salting-in and salting-out of proteins to determine chaotropic and cosmotropic characteristics of ions, but the effects also apply to GAGs, mucins, and other proteoglycans. Studies of the water-air interface, Jones-Dole viscosity B Coefficients for biopolymer, and effects such as arginine-arginine pairing have revealed that models of point-charge electrostatics fail…”
Section: Background: Ion-specific Behavior or Lyotropymentioning
confidence: 99%
“…One is acid promoted Fischer indole synthesis from the corresponding hydrazone intermediates . The other is condensation of tryptamine derivatives with hazardous triphosgene or chloroformates followed by acid promoted Friedel–Crafts acylation . Recently, transition-metal-catalyzed cyclizations have also been reported for the synthesis of these scaffolds to avoid harsh reaction conditions and multistep syntheses …”
Section: Introductionmentioning
confidence: 99%